PERANAN PONDOK PESANTREN REHABILITASI MENTAL ASH-SHIDDIQI DALAM PEMBINAAN KORBAN NARKOBA (Studi Kasus di Pesantren Ash-Shiddiqi Kowel Pamekasan) - Subhan, Moh (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2017)
Environmental factors are become good and badphenomenon that can be kriminogen factors, these factors may be affected by the incidence of crime. Development and social change can also have negative repercussions, namely the emergence of acquaintance-onset juvenile delinquency and actions that lead to criminal acts. One of the forms of juvenile delinquency is such as substance abuse. Drug abuse that occurs is influenced by several factors, one of which is caused by the teenagers did not appreciate and believe in religious requirements, lack of parental supervision, environmental influences and friends to try this new experience is described very pleasant. Therefore, the existence of the boarding school as one of the educational institutions of Islam have a very heavy workload for the overcome the social problems. Boarding school next place to gain knowledge of the religion, it is also useful as a berthing and coaching the young victims of drug abuse, and restore the teens who have good character and moral damage as a result of drug abuse and return to the good way of that have been ridloi by Allah.